Safety of a feed additive consisting of lignosulphonate for all animal species (Borregaard AS) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Birgit Dusemund; Mojca Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal)
Abstract Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety of lignosulphonate, when used as a technological additive (functional group: binders) in feed for all animal species. In two previous assessments, the FEEDAP Panel concluded that the maximum level proposed of 10,000 mg lignosulphonate/kg complete feed is safe for weaned piglets, pigs for fattening, chickens for fattening, laying hens and cattle for fattening, but a margin of safety could not be identified. Consequently, these conclusions could not be extrapolated to other animal species/categories. In the current application, the applicant proposed to reduce the maximum content of lignosulphonate in feed for all animal species to 8,000 mg/kg complete feed. The results of two newly submitted tolerance studies allowed the Panel to conclude that 8,000 mg lignosulphonate/kg complete feed is also safe for dairy cows and salmonids, with a margin of safety of at least 1.25. Considering the results of the studies previously assessed and those of the two new tolerance studies, the FEEDAP Panel concluded that lignosulphonate is safe for all animal species when used at a maximum content of 8,000 mg/kg complete feed.